New bacteria-destructors of phthalates from the area of the Verkhnekamskoye salt deposit: molecular and biological characteristics and biotechnological potential - Plotnikova, E.G.; Yastrebova, O.V.; Korsakova, E.S.; Pyankova, A.A.; Voronina, A.O. (Perm Federal Research Centre Journal, 2019)
The study aims to solve the urgent problem of purification of environmental objects from persistent organic pollutants, in particular phthalates as one of the most representative groups. In the course of the research, sampling and chemical analysis of 12 samples of contaminated / saline soils and potash production wastes (Berezniki, Perm Region) was carried out. 55 strains-destructors of ortho-phthalic acid were isolated from the enrichment cultures (EC), derived from these samples. Based on the analysis of 16S rRNA gene fragment, isolated strains have been identified as members of the genera Arthrobacter, Bacillus, Erythrobacter, Rhodococcus, Idiomarina, Martelella, Marinobacter, Oceanisphaera, Halomonas, Alcanivorax, Stappia and Pseudomonas. 20 strains capable of growth on ortho-PA were selected from the working collection of microorganisms (Laboratory of Molecular Microbiology and Biotechnology, Institute of Ecology and Genetics of Microorganisms, UB RAS). It was established that the isolated and selected strains-destructors of ortho-PA are capable to utilize a number of mono- and polyaromatic hydrocarbons, as well as to grow on media with an increased concentration of NaCl (up to 100%). Eight strains of the genera Halomonas, Pseudomonas, Oceanisphaera, Dietzia, Rhodococcus, Martelella were capable of using phthalic acid esters - dibutyl phthalate (DBP) and diethyl phthalate (DEP) as a substrate. Strains utilized 90-98% DBP and 49-80% DEP (500 mg/l) without salt in the culture medium and in the presence of 50 g/l NaCl. As a result of research, active strains-destructors of phthalates were identified adapted to growth under conditions of increased salinization of the environment, promising for the development of methods for bioremediation of technologically contaminated soils.